History of The Establishment Islamic Boarding Schools In Indonesia - Siti Ulfatun Hasanah; Rahma Wati Ningsih; Nafisah Nur Izzabillah (Pesantren Reviews, 2023)
One kind of Islamic educational institution is an Islamic boarding school, which aims to mold students into individuals who are not only well-educated but also have personalities that benefit both institutions and society as a whole. Islamic boarding schools teach students a variety of religious knowledge as well as formal lessons. However, more importantly, Islamic boarding schools teach students religious knowledge with the goal of making them sound both in this world and the next. Islamic boarding schools also teach students the rules that the kiai has established. Modern Islamic boarding schools in their development are similar to Islamic boarding schools, just that the educational facilities are better. In this Islamic boarding school, teaching uses a classical system of doctrine. Usually, this type of pesantren only considers basic sciences as complementary sciences. Modern education has developed an attitude of seeking knowledge for life and has developed the concept of secularism and individualism. Education is a fundamental field that must belong to every nation. Traditional old patterns, but with the development of the system, modern system innovation. However, this does not mean that a modern pesantren education system negates the traditional education system, which is deeply rooted in pesantren. The modern education system is an addition to the existing traditional education system. In other words, combining tradition and modernity becomes a synergistic education system.